Policy Response and Collaboration in Handling Covid-19 East Kutai Regency With An Adaptive Governance Approach in Disasters - Aji Ratna Kusuma; Paisal Akbar (Pusjar SKPP Lembaga Administrasi Negara, 2021)
The current COVID-19 pandemic condition requires the Indonesian government to act quickly and effectively in dealing with the threat of a crisis; for this reason, the concept of adaptive governance promises a more innovative approach in an effective way to deal with a complex environment. Adaptation in governance is carried out by producing policy products that are swift, efficient, and effective in handling the COVID-19 pandemic. This research aims to find out how the local government of East Kutai Regency applies the concept of adaptive governance with the scope of policies and collaboration between parties in handling the COVID-19 Pandemic. The benefits of research will fill the space for scientific studies related to adaptive governance approaches in handling pandemics through policy products and collaboration between parties within the most basic scope, namely the East Kutai Regency level. This research is qualitative research with the descriptive method; the approach used in this research is a case study approach. For research data analysis, this study used Qualitative Data Software Analysis (QDSA) NVivo 12 Plus. The study results show that the five agencies have carried out their roles to provide adaptive governance. Of the six indicators, each agency has a different percentage level. There are tons of steps that have been taken to prevent the spread and handling of COVID-19 by the government and agencies, as well as layers of society. The involvement of Task Force Teams at all levels, the Police, Military District Commands, Community Organizations, NGOs, and Companies in assisting the prevention and handling of the COVID-19 pandemic running the East Kutai District Health Office shows a form of participation and collaboration in handling the COVID-19 pandemic health disaster. Which is an essential value in realizing adaptive governance.